Tennessee Williams´ late plays: : a revolution against mainstream (DAPesquisa, 2020)
This paper presents the unpublished Tennessee Williams plays in Brazil, they are called late plays in the United States, those written in the third phase of his career. It discusses its reception, the prejudices and the inability to understand its innovative proposals in form and content, arising from the playwright's absorption of his constant presence on the off and off-off-Broadway circuits between 50´s to 70´s. The main features of these plays are the distancing from realism, the mixing of genres and styles, and the exposure of open homosexuality devices, certainly a grasped narrative of counterculture insurrections. The hegemonic reading, the reverence to the major plays, the contemporary tendency of adaptations, the lack of translations and the difficulties of acquiring copyright difficult the study, reading and diffusion of these works in Brazil. Also the Brazilian productions are presented, as well as the scarce academic works on them. Analyzing this unprecedented and countercultural dramaturgy, finally it is concluded that Williams used theatrical poetry of disfigurement to undermine the mimetic conventions of metaphysical dramaturgy and to split with the fictional contents and realistic forms of American Theater.
Keywords: Drama; Williams, Tennessee, 1911-1983; Dramatists, American; Counterculture